The Students' Numeracy Literacy Profile through Visual, Auditory and Kinesthetic Learning Styles - Pratiwi, Ulpha Mega; Pujiastuti, Heni; Novaliyosi, Novaliyosi (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aimed to describe students’ numeracy literacy ability reviewed from visual, auditory, and kinesthetic learning styles. The method used is a qualitative approach with a case study method. The subjects in this study consisted of 73 eighth-grade students at a junior high school in Kelapa Dua, Indonesia, who were selected intentionally based on variations in learning styles and levels of numeracy literacy skills. Data collection was carried out through test numeracy literacy, a questionnaire-style study, and semi-structured interviews. Data were analyzed in a descriptive qualitative way with a triangulation technique to increase the validity of findings. Research results show that students with visual learning tend to achieve higher literacy more numeracy tall compared to students stylish Study auditory and kinesthetic way. Visual students appear more capable of understanding mathematics and developing solution strategies to questions in a way. On the other hand, students are auditory and kinesthetic; many are in the low category, especially because lack of verbal support and concrete activities in the learning process. Research This concludes that the style of Study is influential to the method of student processing and implementing draft numeracy. Findings. This gives important implications in designing learning strategies for adaptive mathematics to suit the needs of students, to improve the quality of numeracy literacy in schools.